(untitled) (Fiep Bulletin - online, 2011)
This study aimed to evaluate changes in neuromuscular control using the Star Excusion Balance Test (SEBT) in individuals who have suffered injuries of the knee or ankle and undergoing physiotherapy treatment. The SEBT consists of eight straight lines of 120 cm long and 3 cm wide, and these straight start in a single point, forming a center, with angle of 45 degrees between each line. The test was performed in one-leg support in the center formed by the intersection of straight lines. It took the name for each line as its direction: anterolateral (AL), anterior (ANT), anteromedial (AM), medial (MD), posteromedial (PM), posterior (PO); posteroinferior lateral (PL) and lateral (LAT). The assessment was bilateral. The SEBT was applied in 20 individuals, 10 belonging to the control group and 10 to the group committed (injury of the knee or ankle) and used the t test for comparison between groups and sides. When comparing the average total of eight straight, there was a difference for the group committed, but not for the control group and the comparison between groups. It is concluded that the SEBT assessment for the sample studied, there are proprioceptive deficits on the injured compared to non-injured side.